CGIAR Climate Insights, Issue 5, 26 March 2024 - Mukherji, Aditi; Marshall, Suzie (CGIAR Climate Change Impact Platform, 2024)
The Climate Impact Platform’s fortnightly roundup of the latest publications on climate change impacts and adaptation, mitigation measures, and the physical science from the literature. We’re tracking trending topics in the climate space and linking them to our work for a food-secure future with a brief comment on the implications of this new research on our portfolio of climate research for development.